2016
DOI: 10.7554/elife.11405
|View full text |Cite
|
Sign up to set email alerts
|

Ret function in muscle stem cells points to tyrosine kinase inhibitor therapy for facioscapulohumeral muscular dystrophy

Abstract: Facioscapulohumeral muscular dystrophy (FSHD) involves sporadic expression of DUX4, which inhibits myogenesis and is pro-apoptotic. To identify target genes, we over-expressed DUX4 in myoblasts and found that the receptor tyrosine kinase Ret was significantly up-regulated, suggesting a role in FSHD. RET is dynamically expressed during myogenic progression in mouse and human myoblasts. Constitutive expression of either RET9 or RET51 increased myoblast proliferation, whereas siRNA-mediated knockdown of Ret induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 110 publications
3
18
0
Order By: Relevance
“…Upon isolation, satellite cells activate and over time become committed myoblasts that are proliferative and able to further differentiate and fuse to form or repair muscle fibers. A previous publication [42] demonstrated that treating myoblasts with the RTK inhibitor sunitinib promoted the cells' differentiation capacity in a model of facioscapulohumeral muscular dystrophy (FSHD) [42]. As our data show that sunitinib and CEP-701 can both increase satellite cell numbers in vitro (Fig.…”
Section: Cep-701 Treatment Enhances Differentiation Of Committed Myobsupporting
confidence: 64%
“…Upon isolation, satellite cells activate and over time become committed myoblasts that are proliferative and able to further differentiate and fuse to form or repair muscle fibers. A previous publication [42] demonstrated that treating myoblasts with the RTK inhibitor sunitinib promoted the cells' differentiation capacity in a model of facioscapulohumeral muscular dystrophy (FSHD) [42]. As our data show that sunitinib and CEP-701 can both increase satellite cell numbers in vitro (Fig.…”
Section: Cep-701 Treatment Enhances Differentiation Of Committed Myobsupporting
confidence: 64%
“…Interestingly, GDNF appeared significantly down-regulated in FSHD biopsies in at least two reports [ 127 , 128 ]. Another study suggests instead that FSHD involves enhanced Ret signaling in myoblasts and proposes Ret inhibitors as a possible therapeutic strategy [ 129 ]. In view of these reports and together with our present findings, it may be relevant to determine whether and to what extent modulation of GDNF/Ret signaling, or of other mechanisms influenced by Fat1 signaling, can have any benefit to alleviate adult muscle symptoms and improve quality of life of FSHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in CRYM have been found to cause hearing loss [86], potentially explaining the occurrence of this phenotype in some FSHD patients. Finally, DUX4 induces the expression of the RET receptor tyrosine kinase (RTK) gene, which promotes the proliferation of satellite cell-derived myoblasts and maintains them in an undifferentiated state [87]. Treatment with sunitinib, an RTK inhibitor, inhibited Ret signalling and rescued differentiation in both mouse myoblasts expressing DUX4 and FSHD patient-derived myoblasts.…”
Section: Muscle Developmentmentioning
confidence: 99%